Analisis Pengaruh Bauran Pemasaran Terhadap Konsumen Dalam Memilih Coffee Shop - Destia Ismayatun Azizah; Cecep Hermana (Jurnal Manajemen DIVERSIFIKASI, 2025)
The era of globalization and intense business competition encourages companies to offer a variety of products, facilities and services to attract consumers. The emergence of the Covid-19 virus outbreak caused many new competitors to emerge, while several coffee shop business owners experienced a decline in turnover and closed their shops. In facing this competition, coffee shops need to innovate and be creative in their concepts and use a marketing mix to attract consumers. Marketing mix is ​​a collection of marketing tools that companies use to promote their products or services to customers. In this case, the focus of this research is on four aspects of the marketing mix, namely product, price, place, and promotion. The products offered by the coffee shop must be able to meet the wants and needs of consumers. Prices must be adjusted to remain profitable for the company. The place or location of the coffee shop is also important in facilitating product distribution. Promotion is a tool for communicating product benefits and influencing consumer buying behavior. The research method used is qualitative data using library techniques and qualitative descriptive analysis. Based on the research results, it was found that a successful coffee shop is one that is able to apply the marketing mix well. In addition, this research also reveals the history and development of coffee shops from Turkey to Europe and England. In developing a coffee shop business, the right strategy is needed to attract buyers and expand the target market. The marketing mix is ​​a strategy that is commonly used by coffee shop companies in achieving marketing objectives. The 4P concept in the marketing mix (product, price, place, promotion) helps companies to plan and manage their marketing efforts effectively. In conclusion, coffee shops need to understand and implement the marketing mix well in order to increase marketing effectiveness, win the competition, and better meet consumer needs. By using the right marketing mix strategy, coffee shops can survive and succeed in a competitive business competition.